The Origin Of Adolescent Criminal Behavior And Its SocioPsychological Factors - Professor Haydarov I.O. (Zien Journals, 2023)
The origin of adolescent behavior and its socio-psychological factors is currently considered one of the global problems. In many countries of near and far abroad, including our Republic, a number of scientific studies have been carried out on the study of juvenile delinquency, which examined the socio-psychological factors that influence the occurrence of such crimes as offenses, alcoholism and drug addiction among minors, crime statistics minors, demographic, legal and territorial characteristics tried in every possible way to scientifically analyze. The results of the study and the proposed ideas serve to form a certain conceptual theory about the socio-psychological factors of juvenile delinquency.
Keywords: demographic; minors; characteristics; delinquency